PENGARUH PORTING PADA CYLINDER HEAD MESIN HONDA TYPE KZR 150CC BERBAHAN BAKAR PERTALITE TERHADAP DAYA TORSI : THE EFFECT OF PORTING ON THE CYLINDER HEAD OF A HONDA KZR 150CC ENGINE USING PERTALITE FUEL ON TORQUE POWER - Muhammad Fuad Hasyim Ashari Fuad Hasyim; Hadi Rahmad; Deny Setiawan (Mechanical Engineering Department Polinema Kediri, 2026)
As the use of the KZR 150CC motorbike experiences a decrease in the torque power produced, it is necessary to make modifications to increase the torque power. This study is to analyze the effect of porting variations on the cylinder head of the Honda KZR 150CC engine using Pertalite fuel on the torque power produced. Porting modifications are carried out on the intake port channel with a diameter of 24.5 mm, 26.5 mm, and 28.5 mm and the exhaust with a diameter of 20.5 mm, 22.5 mm, 24.5 mm. Engine performance testing is carried out using a dyno test to measure torque values at various engine speeds. The test results show that each porting variation produces different torque characteristics. The standard engine has an advantage at low speeds with a peak torque of 11.66 Nm at 6520 RPM, porting 1 excels at medium speeds with a torque of 11.46 Nm at 7270 RPM, while porting 2 shows the best performance at rotations with a peak torque of 12.32 Nm at 7270 RPM. In terms of horsepower, the standard engine has an advantage at low revs with a peak torque of 10.71 HP at 6520 RPM, porting 1 excels at medium revs with a torque of 11.76 HP at 7270 RPM, while porting 2 shows the best performance at revs with a peak torque of 12.62 HP at 7270 RPM.